HOW TO IMPROVE PROBLEM SOLVING ABILITY THROUGH LESSON STUDY? - Dian Mayasari; Abdul Rachman Taufik; Irmawaty Natsir (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The teacher frequently asks questions in the form of algorithms without challenging the student to think at a higher level and nearly never gives daily questions. As can be observed, some teachers have not done competency assessments and hence do not require pupils to accomplish specific competencies. The purpose of this project is to create school collaboration worksheets and examine student responses to these problems, with the goal of implementing learning through the Lesson Study for Learning Community (LSLC) method. This study employs a qualitative approach and a design research method. Design research is divided into two stages: development research and design research. The study's subjects were seventh-grade pupils from SMPN 1 Merauke. This investigation culminated in the development of worksheets on direct comparisons and integers. According to the results of the examination of students' responses to the LKS, some students were able to solve problems effectively, indicating that this LKS was legitimate and useful for use